Análise de citocinas no soro de pacientes com câncer gástrico - HAGE, Pedro Antônio Mufarrej (Universidade Federal do Pará, 2018)
Despite the reduction in the worldwide incidence of gastric cancer, this neoplasm remains the second largest cause of cancer death in the world. Late diagnosis occurs mainly due to the absence of symptoms or the presence of non-specific symptoms in the early stages of the disease. In this case, few effective therapeutic options are available, resulting in high rates of morbidity and mortality. The continuous study of new strategies for the early diagnosis, definition of the prognosis and identification of new therapeutic methods is of great interest in this neoplastic type. In the present study was quantified inflammatory proteins candidate to biomarkers in the serum of 19 patients with gastric adenocarcinoma before surgical resection and 13 healthy individuals as control. The methodology used for quantification of proteins was the MAGPIX system and panels of cancer biomarkers inventoried by the manufacturer (Bio-Plex Pro Human Pro-Cytokine, Chemokine and Growth Factors). In the comparison between patients with gastric adenocarcinoma and control group was observed the levels of IL-1β, IL-1RA, IL-2, IL-6, IL-8, IL-10, IL-12, IL-15, G-CSF, GM-CSF, IFN-γ, MIP1α, RANTES and VEGF were higher in serum of gastric adenocarcinoma patients. According clinicopathological characteristics, was observed elevated levels of IL-5, IL-7, IL-10 and IL-17A in diffuse-type gastric adenocarcinoma in relation intestinal-type. In addition, the association of the expression of the cytokines studied with overall survival (OS) and relapse-free survival (PFS) were performed using the KM Plotter Online Tool. Overexpression of G-CSF, GM-CSF and VEGF in tumor was associated with lower OS and PFS of gastric cancer patients. However, the overexpression of IL-10 was associated only with PFS. Thus, we can conclude that the IL-1β, IL-1RA, IL-2, IL-6, IL-8, IL-10, IL-12, IL-15, G-CSF, GM-CSF, IFN-γ, MIP1α, RANTES and VEGF cytokines are potential biomarkers of gastric cancer, and diffuse-type adenocarcinoma can related to a greater inflammatory response than intestinal-type. Survival analysis suggests that elevated levels of IL-10, G-CSF, GM-CSF and VEGF in serum are potential biomarkers of prognosis in gastric cancerpatients.